Fates of political liberalism in the British post-colony : the politics of the legal complex / edited by Terence C. Halliday, Lucien Karpik, Malcolm M. Feeley. - Halliday, Terence C. (Terence Charles); Karpik, Lucien; Freeley, Malcolm M. (Cambridge University Press, 2012)
What explains divergences in political liberalism among new nations that shared the same colonial heritage? This book assembles exciting original essays on former colonies of the British Empire in South Asia, Africa and Southeast Asia that gained independence after World War II. The interdisciplinary country specialists reveal how inherent contradictions within British colonial rule were resolved after independence in contrasting liberal-legal, despotic and volatile political orders. Through studies of the longue durée and particular events, this book presents a theory of political liberalism in the post-colony and develops rich hypotheses on the conditions under which the legal complex, civil society and the state shape alternative postcolonial trajectories around political freedom. This provocative volume presents new perspectives for scholars and students of postcolonialism, political development and the politics of the legal complex, as well as for policy makers and publics who struggle to construct and defend basic legal freedoms.